Microfinance : perils and prospects - Fernando, Jude L. (New York : Routledge, 2006)
"This book illustrates the historical, political and economic background to our current knowledge on microfinance. The relationship between its prevailing popularity and the consolidation of neoliberal economic ideology worldwide is fully charted. Examining current macroeconomic trends, the volume analyzes the historical confluence of microfinance with feminist notions of empowerment and explores the processes and the extent to which gender hierarchies are institutionalized in development."--Jacket.
Includes bibliographical references and index.
aug 02/05/13; 07/09/16
Loans
Keywords: Microfinance; Credit; Poverty; Women in development; Developing countries